MarkLogic cookbook : querying, searching, and transforming data - Cassel, David M. (O'Reilly Media, 2018)
Learn how to get the most out of MarkLogic with recipes from people who understand this powerful multi-model database platform from the inside out. MarkLogic comes with a broad set of capabilities to help you quickly integrate data from silos, but it takes time to learn how to harness that power. In this three-part series, key members of the MarkLogic team--including engineers who built the database--provide targeted recipes to get you up to speed. In Part 1, you'll learn how to solve real-world problems with XQuery, the functional language for working with hierarchical data structures such as XML. Part 2 helps you solve common search-related problems with recipes that work with MarkLogic 9 as well as with older versions. With recipes in Part 3, you'll explore the multiple ways MarkLogic represents data. XQuery: Gain XQuery peak performance, and explore its use in maps, documents, document security, the task server, and administration Search-related problems: Conduct document searches, score search results, understand how data is used, and search with the Optic API MarkLogic and data: Work with input transformations, tokenization, template-driven extraction, and redaction.